STATIST NARRATIVES AND MAJI MAJI ELLIPSES. - Sunseri, Thaddeus (International Journal of African Historical Studies, 2000)
Focuses the ways on the formation of nationalist historical traditions in Zimbabwe. Contribution to unity during the struggle for independence; Campaign of terror against local peoples by Zimbabwe African National Union-led state; Colonial-era depictions of the depopulation of southeastern districts.